(untitled) (Journal of Global Arts Studies, 2025)
Background: In the era of globalization, intangible cultural heritage (ICH) faces multifaceted challenges, including the disconnect between traditional economic models and modern consumption structures, the erosion of traditional production practices caused by industrialization, and the disparity between traditional cultural creation and contemporary cultural industries. Objective: This study explores pathways for integrating traditional cultural ecosystems with modern industrial frameworks, aiming to establish an innovation-driven model in which economic revitalization supports the systematic preservation and sustainable development of intangible cultural heritage. Methods: Using apicultural intangible cultural heritage as a case study, the research applies industrial ecosystem theory to analyze its globalized value system and representative community practices, while investigating potential pathways for industrial innovation and systematic updates to heritage protection mechanisms. Results: The findings confirm that the construction of industrial ecosystems can establish a systematic framework for the preservation of intangible cultural heritage. Apicultural ICH demonstrates this through institutional structures, culturally grounded documentation practices, and ecosystem-oriented business expansion. Conclusion: This approach provides systematic solutions for safeguarding and developing globally significant intangible cultural heritage projects such as traditional apiculture, while also offering a framework-based perspective applicable to other forms of heritage with clearly defined core value systems.